Firm Performance and Executive Compensation in Australia and Canada - Sharma, Basu; Smith, Anthony (Journal of Comparative International Management)

(untitled) (Management Futures, 2001)
This study reports findings of a comparative study of the influence of firm performance on executive compensation in Australia and Canada. The key finding of the study is that revenue growth rather than profit growth is one of the key determinants of executive compensation.